The Oxford dictionary of music - Salih, Al-Tayyib. 1926-; Kennedy, Joyce Bourne; Rutherford-Johnson, Tim; Oxford eBooks (Oxford : Oxford University Press, 2012)
'The Oxford Dictionary of Music' is a guide for all music lovers and performers, both amateur and professional. It brings together 12,500 entries covering musical subjects of all kinds in an authoritative and accessible way.
Previous edition: published as The concise Oxford dictionary of music. 2007.
Description based on print version record.
Keywords: Music -- Dictionaries; Electronic books